2019
DOI: 10.1017/thg.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

Excess Infant Mortality of Twins Over Singletons in Arab Countries: The Evidence of Relative Survival Methods

Abstract: There are no studies and only limited data that compare the difference in mortality between twins and singletons in the Arab world. We studied the survival of 306,966 children, including 9,280 twins, over the period 1970–2013 in six Arab countries (Algeria, Egypt, Iraq, Mauritania, Sudan and Tunisia) based on the Multiple Indicator Cluster Survey (MICS) database. With the use of relative survival models, we estimated the mortality of twins relative to singletons by including socioeconomic and demographic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The most common causes of such an excess of deaths are biological, such as complications at birth (Uthman et al, 2008), and low birth weight (Parker et al, 2001). Furthermore, this partial finding (ratio level) was consistent with those reported by Kleinman et al (1991), andChellai &Boudrissa (2019). Consequently, we confirmed that twins are at an increased risk of under-five-child death compared to singletons across all birth orders (women's parities) in the selected Arab countries.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The most common causes of such an excess of deaths are biological, such as complications at birth (Uthman et al, 2008), and low birth weight (Parker et al, 2001). Furthermore, this partial finding (ratio level) was consistent with those reported by Kleinman et al (1991), andChellai &Boudrissa (2019). Consequently, we confirmed that twins are at an increased risk of under-five-child death compared to singletons across all birth orders (women's parities) in the selected Arab countries.…”
Section: Discussionsupporting
confidence: 84%
“…As a comparison between twins and singletons, all previous studies stated that twins (and triples) have a higher risk of death than singletons during childhood (first year, underfive). Chellai & Boudrissa (2019) used relative survival approaches to confirm the excess deaths of twins over singletons in these six Arab countries. The most common causes of such an excess of deaths are biological, such as complications at birth (Uthman et al, 2008), and low birth weight (Parker et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation